(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The hospitality industry, encompassing lodging, food and beverage, entertainment, and more, is dedicated to crafting memorable experiences for individuals and groups far from their usual residences. At its core, this industry is committed to impeccable customer service and satisfaction, closely interconnecting with the world of tourism. Within this expansive realm, restaurants, as essential components of food and beverage services, occupy a pivotal role. This paper explores the evolution of dining and its profound impact on the hospitality industry.